2008
DOI: 10.1007/s00277-008-0669-3
|View full text |Cite
|
Sign up to set email alerts
|

L-Asparaginase in the treatment of refractory and relapsed extranodal NK/T-cell lymphoma, nasal type

Abstract: There is no standard salvage regimen for patients with refractory and relapsed extranodal NK/T-cell lymphoma (NKTCL), nasal type. This study was conduced to evaluate the efficacy of L-asparaginase-based regimen as a salvage regimen, on refractory and relapsed extranodal NKTCL, nasal type. Between March 1996 and March 2008, 45 patients with refractory and relapsed extranodal NKTCL, nasal type, were studied retrospectively. All patients were treated with L-asparaginase-based salvage regimen. Thirty-nine patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 23 publications
2
93
1
Order By: Relevance
“…With a novel risk stratification and more accurate staging methods, including improved imaging techniques and molecular markers, [35][36][37] future research should aim to determine whether these patients at high risk of systemic failure can benefit from innovative, more effective systemic therapies, such as new chemotherapeutic regimens and molecular targeted therapies. [38][39][40][41] The incidence of CNS involvement was largely diverse, mainly depending on the pathological subtype and stage of NHL. 42,43 Similarly to another study, 44 we found a very infrequent CNS relapse (1%) in patients with early stage nasal NK/T-cell lymphoma, not justifying the use of CNS chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…With a novel risk stratification and more accurate staging methods, including improved imaging techniques and molecular markers, [35][36][37] future research should aim to determine whether these patients at high risk of systemic failure can benefit from innovative, more effective systemic therapies, such as new chemotherapeutic regimens and molecular targeted therapies. [38][39][40][41] The incidence of CNS involvement was largely diverse, mainly depending on the pathological subtype and stage of NHL. 42,43 Similarly to another study, 44 we found a very infrequent CNS relapse (1%) in patients with early stage nasal NK/T-cell lymphoma, not justifying the use of CNS chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…According to their latest publication [52], one to six cycles of chemotherapy with L-asparaginase, vincristine, and dexamethasone followed by IF-RT at a median dose of 50 Gy (range 30-60 Gy) were planned. Forty-one patients were evaluated in the study, with no statistical consideration for the sample size being reported.…”
Section: Clinical Trials In the Early 2000smentioning
confidence: 99%
“…Furthermore, the relapse rate was high in both groups. The combination of CHOP and etoposide demonstrated a CR rate of 45% with a 3-year OS rate of 59% for nasal-type NK-cell lymphoma [Yong et al 2009]. …”
Section: Treatment Of Nk/t-cell Lymphomasmentioning
confidence: 99%